Efficient formation of C–S bond using heterocyclic thiones and arynes. (22nd January 2021) - An, Yu; Xu, Gang; Cai, Menglu; Wang, Shihui; Wang, Xiao zhong; Chen, Yingqi; Dai, Liyan
Abstract: Phenylthio heterocyclic compounds are widely used because of their diverse biological activities and medicinal prospects. Here, a facile method was reported. An arylation of 1, 3, 4-oxa(thia)diazol-2-thiones reacting with arynes to build C(aryl)-S bonds in the presence of CsF had good yields and excellent selectivity. The reaction was completed in short time without using expensive reagents and catalysts. Present reaction system is an efficient procedure to process phenylthio heterocyclic compounds and reveals a sustainable method and better application prospects in future organic synthesis. Graphical abstract: Image 1 Highlights: The method has good yield and excellent selectivity. The reaction shows high tolerance for common functional groups. The reaction reduces the cost of reagents and the energy consumption. The method is a facile synthesis approach to build C(aryl)-S bonds between aromatic and heterocyclic compounds. The method can be used for more preparations of heterocyclic phenyl sulfides with functional activities.